Perancangan Sistem Informasi Account Officer Berbasis Web Menggunakan Design Science Research - Antonius Bayu Saputra; Johan Jimmy Carter Tambotoh (STMIK Banjarbaru, 2025)
With the continuous evolution of the digital era and the rapid development of modern technology, the need for efficient information systems has become increasingly vital, especially in the banking sector. This study aims to design a web-based Account Officer (AO) information system for BPR Weleri Makmur to enhance the efficiency of lead generation and customer data management. Previously, AOs relied on manual approaches such as brochure distribution and direct visits, which were less effective and time-consuming. The research applies the Design Science Research Methodology (DSRM), consisting of stages including problem identification, goal definition, system design, demonstration, evaluation, and communication. The system includes features for customer data management, visit scheduling, multi-channel communication (WhatsApp, SMS, and email), performance reporting, and data analytics to identify potential clients. Based on blackbox testing, all functionalities operate as expected. The implementation improves AO productivity, speeds up customer analysis, and supports data-driven decision-making, contributing to the advancement of web-based banking information systems.Keywords: Information System; Account Officer; Web Base; Design Science Research MethodologyAbstrakPerkembangan teknologi digital mendorong kebutuhan akan sistem informasi yang efisien, termasuk di sektor perbankan. Penelitian ini bertujuan merancang sistem informasi Account Officer (AO) berbasis web pada BPR Weleri Makmur untuk meningkatkan efektivitas proses pencarian dan pengelolaan data nasabah. Sebelumnya, kegiatan AO masih dilakukan secara manual melalui penyebaran brosur dan kunjungan langsung yang kurang efisien. Metode yang digunakan adalah Design Science Research Methodology (DSRM) dengan tahapan identifikasi masalah, penentuan tujuan, perancangan, demonstrasi, evaluasi, dan komunikasi. Pengujian dilakukan menggunakan metode Blackbox untuk memastikan kesesuaian fungsi sistem. Hasil penelitian menunjukkan bahwa seluruh fitur berjalan dengan baik dan mampu membantu AO dalam mengelola data nasabah, mempercepat proses analisis calon nasabah, serta mendukung pengambilan keputusan berbasis data. Sistem ini berkontribusi dalam peningkatan kinerja perbankan melalui penerapan teknologi informasi berbasis web.